Dahlia tamaulipana (Asteraceae, Coreopsideae), a new species from the Sierra Madre Oriental biogeographic province in Mexico - Reyes-Santiago, Jerónimo; Islas-Luna, María De Los Ángeles; Macías-Flores, Rafael Guadalupe; Castro-Castro, Arturo (Phytotaxa, 2018)
Dahlia tamaulipana (Asteraceae, Coreopsideae) a new species from Sierra Madre Oriental in Tamaulipas, Mexico, is described. The new species is morphologically similar to D. tubulata, but differs by developing stems evidently hexagonal and villous in the upper portion of the nodes and the base of the petioles, the internodes reach 3–5.5 × 1–1.5 cm, the stipels are present from the first to the third pair of leaflets, the synflorescence develops (1–)15–25 heads, the heads reach 6.5–10 cm wide across the extended rays, and clavate cypsela with crown-shaped pappus. Both species inhabit the northern portion of the Sierra Madre Oriental, however they are not sympatric and do not share ecological preferences and phenological behavior. The description of the new species is accompanied with photographs, a chromosome count, and a distributions map and a key for Dahlia in Sierra Madre Oriental.